ANALISIS KESESUAIAN PENEMPATAN DENGAN KOMPETENSI PEGAWAI PADA KANTOR KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Mutmainnah Mutmainnah (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
The purpose of this study was to determine the level of suitability of placements with employee competencies at the Watang Sidenreng District Office, Sidenreng Rappang Regency and to determine the factors that influence the level of placement suitability with employee competencies at the Watang Sidenreng District Office. The population in this study were all employees at the Watang Sidenreng District Office, Sidenreng Rappang Regency, totaling 40 employees. The type of research is associative / looking for a relationship, while the basis of the research is a survey. The analysis technique used is quantitative by describing the results of the processed data. The results showed that the level of suitability of the placement with the competence of the employee was very appropriate at 78.75%. This can be seen from the main tasks and functions are in accordance with 68.12%, planning is in accordance with 68.12%, supervision is in accordance with 74.37%, evaluation is in accordance with 75% while the influencing factors are education is in accordance with 65.62% and work experience is appropriate 57.5%.